Total Alkaloid Determination in Ethanolic Extract of Cocoa (T. cacao) and Robusta Coffee (C. canephora) Beans using TLC-Densitometric Method - Setyaningrum, Lindawati; Purwanti, Aliyah; Jannah, Roudatul; Diana, Nadha Nofa; Wardani, Astrid Kusuma; Armandari, Inna (Universitas Islam Indonesia, 2026)
Alkaloids are a major class of bioactive secondary metabolites commonly found in various natural products, including cocoa (Theobroma cacaoL.) and robusta coffee (Coffea canephora). These compounds have been widely reported to exhibit important pharmacological activities, including antioxidant, antidiabetic, antifungal, and antibacterial effects, making them valuable candidates for the development of pharmaceutical and functional herbal products. This study aimed to provide reliable quantitative data on the total alkaloid content of ethanolic extracts from cocoa (Theobroma cacao L.) and robusta coffee (Coffea canephora) beans using the TLC-densitometric method, thereby supporting the standardization, quality control, and potential pharmaceutical applications of these natural materials. However, alkaloid was extracted and fractioned from cocoa and robusta coffee beans using ethanol and chloroform. The total alkaloids in the ethanolic extracts of cocoa and robusta coffee beans were identified by TLC-Densitometry, with average Retardation factors (Rf) of 0.321 and 0.771, respectively. Caffeine was used as a standard. The quantification of total alkaloid in the ethanolic extract of cocoa and robusta coffee beans was 2.003% per 50 mg and 11.713% w/w per 10 mg extract, respectively. In summary, cocoa and robusta coffee beans show promising potential as herbal medicines because they contain substantial levels of pharmacologically active alkaloid compounds.